STUDY OF RELATED FACTORS AND CLINICAL FEATURES OF SCABIEI IN SOC TRANG CITY IN 2025 - Nguyen, Tri Qui; Nguyen, Phuong Nga; Pham, Thuy Nga; Truong, Le Anh Tuan (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Scabies is a dermatological disease caused by the parasite Sarcoptes scabiei hominis. This study aims to identify associated factors and describe the clinical characteristics of scabies in Soc Trang City in 2025. Objectives: To describe the clinical features and analyze factors associated with the prevalence of scabies in Soc Trang City. Materials and methods: This was a descriptive analytical study conducted on 165 individuals residing in Soc Trang City from January to March 2025. Participants were selected using systematic random sampling and were assessed through interviews, clinical examinations, and parasitological tests using microscopy. Results: The prevalence of scabies was 35.8%. Factors associated with scabies included: households with ≥4 members, contact or sharing personal items with infected individuals, low household income, and low educational attainment. The education level of parents was related to the prevalence of scabies in children aged ≤18 years. The mean age of participants was 43.19±24.77 years, with females being more affected than males. The average duration of illness was 8.8±5.84 weeks. Typical scabies accounted for 83.1% of cases, and severe cases made up 61%. The most common lesion was scabetic papules. Lesions were most frequently found on the feet and hands. The detection rate of Sarcoptes scabiei by light microscopy was 15.25%. Conclusion: Factors such as household size, contact with infected individuals, low socioeconomic status, and low educational level of individuals and their parents were associated with scabies prevalence. Identifying risk factors and clinical characteristics can improve diagnosis, treatment, and control of the disease in the community.